(untitled) (Research, Society and Development, 2024)
Phytotherapy is a complementary therapy that uses medicinal plants for the prevention and rehabilitation of health problems, being an ancient modality and widespread throughout the generations. Therefore, it can be applied to simpler or more complex care, including palliative care with action aimed at relieving symptoms and promoting patients’ quality of life. The objective of the study was to search the literature for the application of phytotherapy in patients undergoing palliative care. This is an integrative literature review of an exploratory nature with a qualitative approach with data collected from the electronic databases SciELO (Scientific Electronic Library Online), VHL (Virtual Health Library) and PubMed (U.S. National Library of Medicine), during the period of 2019 to 2024, obtained between May and June 2024. The results found 73 articles that, after careful review, 63 were excluded, ultimately selecting 10 articles that demonstrate the use of phytotherapy in palliative care, providing benefits with analgesic, antitumor, anti- inflammatory, antioxidant and cachexia, in addition to its main symptoms (pain, fatigue, anxiety, depression, among others) that can be treated with herbal medicines and points out the challenges for the use and adequate prescription, insufficient scientific knowledge of health professionals about this therapy and the need to develop new studies in this field of research. It is concluded that the application of phytotherapy in palliative care is significant and viable for providing relief and increasing survival, in a way that improves their quality of life and maintains the autonomy of these patients. Still, there are barriers that both health professionals and users need to overcome, with the nurse’s role in creating a bond between the two parties and with ongoing health education and encouragement for the development of new research in this area.